(untitled) (Agroindustrial Science, 2022)
The toxicity of microorganisms such as aflatoxins found in various varieties of food that are currently widely consumed in Peru as in the world. Many of the foods contaminated with aflatoxins cause diseases, one of the main ones being carcinogenicity. This study aimed to evaluate the effect of ozone/air and UV concentration on the remediation of aflatoxins in different cereals or grains for human consumption. This study reviews how a new reactor can be developed that degrade and detoxify into more aflatoxins, however, many studies have verified that the harmful effects of AFB1 can be greatly reduced by UV irradiation in the photodegradation reactor, and the reactor can be applied on a large scale in the detoxification of AFB1 of many kinds of cereal, as well as in sewage. Therefore, there has been a growth in the development of new biofilm-type and closed reactors to reduce the amount of this toxin in food. The creation of new bioreactors such as the fluidized bed one is very promising for the decontamination of aflatoxins in cereals and would be less dangerous for consumers.